THE HUGE CORE AND TECTONIC EVOLUTION OF MERCURY - Vidmachenko, Anatoliy (Collection of scientific papers «ΛΌГOΣ», 2025)
A distinctive feature of Mercury’s internal structure is its metallic core, which occupies about 85% of the planet’s radius. The core accounts for up to 75% of the planet’s mass. Mercury’s core consists mainly of iron and up to 20% of nickel impurities. It is believed that elements such as sulfur and silicon may be present in the core within 5%. They can lower the melting point of the iron-nickel mixture. And this is important in order to explain the partially liquid state of its core. To explain the high content of metals compared to silicates, it was proposed that Mercury’s predecessor had a more typical ratio of metals to silicates. However, at the initial stage of its history, this body experienced a powerful collision with another large body. After such an impact, a significant part of the original silicate mantle and crust could have been “stripped off”, leaving only a metallic core with a thin shell. Recent data suggest that Mercury’s vast core is not homogeneous, but has a differentiated structure, divided into a solid inner and a liquid outer part. The Mariner 10 spacecraft detected a weak global magnetic field, formed by convective motions of an electrically conductive liquid in the planet’s core. This should occur only if there is at least a partially molten core. The differences in parameters between the smooth plains in the inner ring of the Rachmaninoff Basin and the surrounding surface are evidence that these internal smooth plains are the product of relatively young volcanism. The presence of a solid part of the inner core indicates that the core of Mercury is gradually cooling and starting to crystallize from the middle. The surface of Mercury is a kind of reflection of the chronicle of the rather turbulent history of the entire planet, which is manifested by numerous impact craters, the absence of an atmosphere, large plains and unique tectonic structures.